Insulin therapy in organ donation and transplantation. Issue 7 (14th April 2019) - Shapey, Iestyn M.; Summers, Angela; Yiannoullou, Petros; Bannard‐Smith, Jonathan; Augustine, Titus; Rutter, Martin K.; van Dellen, David
Abstract: Hyperglycaemia is common in hospitalized individuals, and is often caused by physiological stress associated with critical illness or major surgery. Insulin therapy is an established treatment for hyperglycaemia and acute hyperkalaemia, and has also been used for myocardial dysfunction resistant to inotropic support. Insulin is commonly used in both organ donors and transplant recipients for hyperglycaemia, but the underlying knowledge base supporting its use remains limited. Insulin therapy plays an important yet poorly understood role in both organ donation and transplantation. Tight glycaemic control has been extensively studied in critical care over the past 15 years; however, this has not yet translated into the field of transplantation, where patients are more unwell and where improved outcomes remain an ongoing challenge. Insulin therapy and optimization of glycaemic control represent important areas for future hypothesis‐driven research into organ donation and transplantation, such as amelioration of ischaemia‐reperfusion injury, rejection and infection.